Melatonin promotes blood-brain barrier integrity in methamphetamine-induced inflammation in primary rat brain microvascular endothelial cells - Jumnongprakhon P. (2017)
© 2016 Elsevier B.V. All rights reserved. Melatonin is a neurohormone and has high potent of antioxidant that is widely reported to be active against methamphetamine (METH)-induced toxicity to neuron, glial cells, and brain endothelial cells. However, the role of melatonin on the inflammatory responses which are mostly caused by blood-brain barrier (BBB) impairment by METH administration has not been investigated. This study used the primary rat brain microvascular endothelial cells (BMVECs) to determine the protective mechanism of melatonin on METH-induced inflammatory responses in the BBB via nuclear factor-KB (NF-κB) and nuclear factor erythroid 2-related factor-2 (Nrf2) signaling. Herein, we demonstrated that melatonin reduced the level of the inflammatory mediators, including intercellular adhesion molecules (ICAM)-1, vascular cell adhesion molecules (VCAM)-1, matrix metallopeptidase (MMP)-9, inducible nitric oxide synthase (iNOS), and nitric oxide (NO) caused by METH. These responses were related to the decrease of the expression and translocation of the NF-κB p65 subunit and the activity of NADPH oxidase (NOX)-2. In addition, melatonin promoted the antioxidant processes, modulated the expression and translocation of Nrf2, and also increased the level of heme oxygenase (HO)-1, NAD (P) H: quinone oxidoreductase (NQO)-1, γ-glutamylcysteine synthase (γ-GCLC), and the activity of superoxide dismutase (SOD) through NOX2 mechanism. In addition, we found that the protective role of melatonin in METH-induced inflammatory responses in the BBB was mediated through melatonin receptors (MT1/2). We concluded that the interaction of melatonin with its receptor prevented METH-induced inflammatory responses by suppressing the NF-κB signaling and promoting the Nrf2 signaling before BBB impairment.